Blood rubies [large type] - Cleland, Jane K. (Cleland, Jane K. Josie Prescott antiques mysteries., 2015)
Ana Yartsin's Fabergé egg-shaped cakes have brought national attention, as has the fact that her family owns the Fabergé Spring Egg snow globe. A reality TV show about her bakery will show Ana planning desserts for her friend Heather's wedding to investment guru, Jason Ferris. Hired by Ana to appraise the precious antique, Josie Prescott arrives at Ana's home to find Jason murdered and the snow globe smashed. And the bits and pieces reveal that it was a fake.